Draft Annual Plan for 1975-76 Part II Government of Nagaland - Planning Commission (Planning Commission, 1974)
Nagaland is a Billy State except a narrow trip foot-hills bordering Assam. Annually an area of about lakh hectares is put under cultivation of which about 23,000 Sq. are under permanent cultivation and the rest is under Jhum or shift in cultivation.
Government of Nagaland, Planning and Co-ordination Department